Soft X-rays spectroscopy with a commercial CMOS image sensor at room temperature - Sofo Haro, M.; Alcalde Bessia, F.; Pérez, M.; Blostein, J.J.; Balmaceda, D.F.; Gómez Berisso, M.; Lipovetzky, J. (Elsevier, 2020)
Fil: Sofo Haro, M. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina